Effects of Self Regulatory Learning, Personal Goal Setting and Perceptions of the Teaching Profession on Literacy of Vocational Teachers - Milla Anifatul Rosada; Setiadi Cahyono Putro; Hari Putranto (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
Literacy of the vocational teachers can certainly improve aspects of knowledge, skills and attitudes of a person thus the main competence of teachers can be achieved. The objective of this study was to reveal the relationship and the contribution of self regulatory learning (X1), personal goal setting (X2), and perception of the teaching profession (X3) with the literacy of vocational teachers (Y). This study used a quantitative method with descriptive correlational research design. The sample of this study consisted of the students of the bachelor degree program of Electrical Engineering Education in the Faculty of Engineering, Universitas Negeri Malang in the academic year of 2014 with 114 respondents. Data collection techniques used a questionnaire adapted using a likert scale. Data analysis used multiple linear regression analysis. The results showed there was a significant relationship between X1, X2, and X3 with Y either partially or simultaneously. The ability of self regulation learning, personal goal setting, and perceptions of the teaching profession contributed 56.3% to achieving literacy of vocational teachers, with a variable sequence that contributes from high to low were self regulatory learning, perceptions of the teaching profession and personal goal setting.